Legalitas Perkawinan Campuran Yang Dilangsungkan Di Luar Negeri Dan Pengakuannya Di Indonesia - Ariyanti, Lukita; Dian Ratu Ayu Uswatun Khasanah (Diktum: Jurnal Ilmu Hukum, 2026)
This study analyzes the legality and recognition mechanism of mixed marriages conducted abroad under Indonesian law. Employing a normative legal method with statutory and conceptual approaches, the research reveals that recognition of such marriages depends on conformity with three elements: the law of the country where the marriage was celebrated, Indonesian national law, and the public order principle. Differences in legal systems and weak regulatory harmonization create legal conflicts and uncertainty in practice. These conditions adversely affect the legal status of the parties, including their civil rights and citizenship issues. Furthermore, existing legal administrative mechanisms for registration and recognition have not been fully effective in ensuring legal certainty. As a result, mixed-marriage couples often face obstacles in obtaining population administration documents and exercising their rights. Therefore, legal harmonization is urgently needed through regulatory reform, institutional strengthening, and a human rights–based approach to protect the fundamental rights of transnational couples.